PENGARUH PENGGUNAAN COIL BOOSTER, PENAMBAHAN METANOL DALAM PREMIUM DAN VARIASI PUTARAN MESIN TERHADAP EMISI GAS BUANG CO DAN HC PADA YAMAHA MIO SPORTY TAHUN 2007 - Isa, Mohammad (Jurnal Nosel, 2013)
The purpose of this study are investigate effect of usage booster coil, adding methanol in premium and interaction at 1500 rpm, 2500 rpm, 3500 rpm and 4500 rpm, to low CO and HC emissions on Yamaha Mio Sporty 2007. Component ware used for data analysis includes: ignition system (standard coil and installation booster coil), addition methanol (10% (M10), 20% (M20), 30% (M30) and 40% (M40)), variations of rotation engine speed (1500 rpm, 2500 rpm, 3500 rpm and 4500 rpm), and exhaust emissions (CO and HC). Based on the results of research at 1500 rpm, 2500 rpm, 3500 rpm, 4500 rpm, We can concluded that usage booster coil, addition methanol in premium and interaction can affect CO and HC emissions, so it tends to fall.